Synergistic Incorporating RuO2 and NiFeOOH Layers onto Ni3S2 Nanoflakes with Modulated Electron Structure for Efficient Water Splitting. Issue 9 (22nd July 2022) - Zhang, Hongmei; Chen, Chu; Wu, Xueyan; Lv, Changwu; Lv, Yan; Guo, Jixi; Jia, Dianzeng
Abstract: Synergistic electronic modulations is an effective strategy to develop efficient and stable electrocatalysts for the electrochemical hydrogen production via water splitting. Herein, tremella‐like Ni3 S2 @RuO2 and Ni3 S2 @NiFeOOH heterostructures catalysts are constructed on Ni foams (NF) by coupling RuO2 and NiFeOOH on Ni3 S2 nanoflake arrays. The resulting Ni3 S2 @RuO2 /NF electrode exhibits top‐level hydrogen evolution reaction electrocatalysis with an extremely low overpotential of 12 mV at 10 mA cm −2 and a Tafel slope of 30.7 mV dec −1, as well as the as‐obtained Ni3 S2 @NiFeOOH/NF electrode with tunable binding energy for OH* intermediates shows remarkable oxygen evolution reaction electrocatalysis with an overpotential of 227 mV at 10 mA cm −2 . The electrolyzer employing Ni3 S2 @RuO2 /NF electrode for cathodic H2 production and Ni3 S2 @NiFeOOH/NF for anodic O2 production merely needs a low voltage of 1.47 V to drive 10 mA cm −2 with excellent durability. The combined theoretical calculation and X‐ray photoelectron spectroscopy investigation reveal that heterogeneous configuration can induce electron transfer from Ni3 S2 to RuO2 through NiRu/SRu bonds, and thus tailor the d‐band center and optimize the activated H2 O/H* Gibbs free energies for enhanced hydrogen evolution reaction on Ni3 S2 @RuO2 . This study may shed new light on the construction of heterostructures as highest‐performing electrocatalysts and offer unique insight into the theory mechanism. Abstract : Novel tremella‐like Ni3 S2 @RuO2 /NF and Ni3 S2 @NiFeOOH/NF heterostructures catalysts by coupling RuO2 and NiFeOOH on Ni3 S2 nanoflakes exhibit excellent hydrogen and oxygen evolution reaction catalytic activity. Heterogenous configuration induces electron transfer from Ni3 S2 to RuO2 through NiRu/SRu bonds, and thus tailors the d‐band center and optimizes the activated H2 O/H* Gibbs free energies for enhanced hydrogen evolution reaction on Ni3 S2 @RuO2 .